A contemporary profile of primary progressive multiple sclerosis participants from the NARCOMS Registry. (June 2018) - Salter, Amber; Thomas, Nina P; Tyry, Tuula; Cutter, Gary R; Marrie, Ruth Ann
Background: Primary progressive multiple sclerosis (PPMS) represents 10%–15% of all multiple sclerosis (MS) diagnoses. Information regarding socio-demographic and clinical characteristics of persons with PPMS is limited. Objective: To characterize persons with PPMS in the North American Research Committee on Multiple Sclerosis (NARCOMS) Registry. Methods: We compared demographic and health-related characteristics of NARCOMS Registry participants reporting PPMS in the spring 2015 update survey with those reporting relapsing-remitting multiple sclerosis (RRMS) and secondary progressive multiple sclerosis (SPMS), with characteristics of published PPMS cohorts. Results: Of 8004 responders, 6774 self-reported a clinical course of PPMS, SPMS, or RRMS. The PPMS cohort ( n  = 632, 9.3%) reported a mean (standard deviation (SD)) age of 64.3 (8.9) years; 62.7% were female; the SPMS and RRMS cohorts were younger and had a higher proportion of females. The NARCOMS PPMS cohort differed in age, time from onset and diagnosis, and proportion of females compared to population-based and clinical trial cohorts. Median (25%, 75%) number of comorbidities was 2 (1, 2) for each cohort with vascular comorbidities being most frequently reported. Conclusion: The NARCOMS population provides a different perspective on persons with PPMS than clinical trials. A better understanding of the characteristics of persons with PPMS may help address unmet needs in this population.